TERAPAN PERAKITAN KOMPUTER BAGI SISWA KELAS X DI SMK MUHAMMADIYAH LOA JANAN - Salwa Jannata, Agus Santoso; Ihdansyah Noor, Muhammad (DiJITAC : Digital Journal of Information Technology and Communication, 2023)
Abstract The fact is generally that computer assembly in schools, indeed easy to say, see and observe, but it is not easy to practice. This matter also did not escape the students of SMK class X majoring in Computer Network Engineering in Loa Janan, Kutai Kartanegara Regency. The first problem is an error in the installation orientation of components such as the processor, RAM, and expansion cards, Second, it does not use an anti-static armband so that it can damage sensitive components. Third, errors in connecting the power cord that can cause a short circuit in the components. Fourth, the installation of the heat sink is still wrong so that it can cause excessive temperatures and potentially damage the processor. Fifth, an error in connecting the casing cable to the motherboard. Sixth, the use of thermal paste that is not appropriate and even forgotten. This research method uses a type of qualitative research using an experimental approach with stages of introduction, contextualization, real action, reflection and follow-up. The results of this study are that students of SMK Muhammadiyah Loa Janan can show a good understanding related to computer assembly, from introduction to follow-up. They are able to identify components, execute assembly carefully, and respond to experiences with a variety of diverse feelings and, students can demonstrate a commitment to continuous learning and developing their skills through diverse follow-up plans. So the results of this study show a positive picture and potential development of technological learning, especially in the assembly of mini PCs in the future.